Population and Diagnostic Characteristics of Polycystic Ovary Syndrome and Hyperandrogenism - Crystal Clark Douglas; Juan Ulises Rojo (Women's Health Reports)
Background: Polycystic ovary syndrome (PCOS) is an endocrine disorder frequently characterized by hyperandrogenism that presents acute and chronic health risks. International guidelines for the assessment of PCOS endorse Rotterdam criteria for diagnosis, necessitating thorough clinical and laboratory evaluation. Heterogenous PCOS phenotypes, multiple providers, and subjective visual assessment of PCOS-related symptoms further challenge diagnostic practices. This study describes the patient population with hyperandrogenism and evaluates if Rotterdam criteria are useful to clinicians. Materials and Methods: A retrospective population-based study of electronic medical records retrieved from January 1, 2019, through December 31, 2023, of female patients aged 18–99 years with a diagnosis of PCOS or evidence of clinical hyperandrogenism seen at a single academic medical center was evaluated. Demographic characteristics, clinical presentation, and selected laboratory values retrieved within 90 days of diagnosis were compared between groups. Results: A population of 2,278 patients were evaluated, out of which 41.4% received a diagnosis of PCOS or presented with hyperandrogenism (58.6%). PCOS patients were mostly found to be White, obese, and aged 18–39 years. Diagnostic evidence of hyperandrogenism was limited; elevated free testosterone and clinical hyperandrogenism were reported in 8.1% and 7.8% of PCOS patients, respectively. Comorbidities including hypertension (24.23%), hyperlipidemia (11.72%), and type 2 diabetes (9.79%) were most prevalent among the sample population. Conclusions: Consistent with prior research, our results demonstrate gaps in diagnostic practices and support the need for future studies that evaluate barriers to diagnosis in clinical practice and increase education to support patient’s involvement in the diagnostic practices.